Double-Lock Strategy Applied to Optical Spectral Phase and Delay Encoding - Francisco Abbade, Marcelo Luis [UNESP]; Bueno Bobadilla, Leonardo Diogo [UNESP]; Martao, Vanessa Beatriz [UNESP]; Carvalho, Daniel Orquiza de [UNESP]; Ferreira, Andre Alves [UNESP]; Bonani, Luiz Henrique; IEEE (Ieee, 2017)
Physical layer encryption (PLE) is a promising technology for increasing the security of communication networks. An important goal of PLE is to establish a mechanism that allows authorized users to understand cyphered messages. In this work, we show that this objective may be successfully accomplished by applying a double-lock strategy to the recently proposed optical spectral phase and delay encoding (SPDE) technique. The main feature of this strategy is that authorized users do not need to exchange a cryptographic key to achieve a safe communication. Computer simulation results suggest this double-lock approach may be effectively used by metropolitan area network end users deploying SPDE encrypted 100 Gb/s signals.
Keywords: optical communications; optical security and encryption; optical networks